The Influence of Live Streaming and Flash Sales on Purchasing Decisions on the TiktokShop Application - Selly Septiani; Salsabilla Rahmawati; Farah Noor Ayuningtyas (Indonesian Journal of Business Analytics, 2024)
TikTok has an impact on growing its market share and providing opportunities for TikTok to develop its business through online shopping called TikTok Shop. This research aims to determine the relationship between live streaming and flash sales on purchasing decisions on the TiktokShop application. This research is quantitative.  The data collection method in research is through distributing of online questionnaires. The number of samples collected was 120 respondents in the city of Cirebon who had made purchases during live streaming and flash sales on the TiktokShop application. This research uses a non-probability sampling method, namely purposive sampling. Test data analysis using the Structural Equation Modeling (SEM) theoretical model on SmartPLS 3 software. Based on the research results, it can be concluded that the live streaming variable has a positive and significant influence on purchasing decisions on the TiktokShop Application, and the flash sales variable also has a positive and significant influence on purchasing decisions on the TiktokShop Application.